2016
DOI: 10.1111/apa.13467
|View full text |Cite
|
Sign up to set email alerts
|

Children born preterm and full term have similar rates of feeding problems at three years of age

Abstract: Using a parental report instrument showed that the prevalence of feeding problems in three-year-old preterm children was low and similar to that of term children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
37
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 22 publications
3
37
1
4
Order By: Relevance
“…The recent article by Nieuwenhuis and colleagues investigated the prevalence of feeding problems in the Netherlands among a sample of preterm infants born <32 weeks' gestation compared to a sample of full‐term infants at the age of 3 years . Contrary to previous studies that report an incidence of feeding problems of 23% or higher among very preterm infants , there was a low incidence of feeding problems, with only 11% of preterm infants and 15% of full‐term infants experiencing feeding challenges in the current study.…”
contrasting
confidence: 67%
“…The recent article by Nieuwenhuis and colleagues investigated the prevalence of feeding problems in the Netherlands among a sample of preterm infants born <32 weeks' gestation compared to a sample of full‐term infants at the age of 3 years . Contrary to previous studies that report an incidence of feeding problems of 23% or higher among very preterm infants , there was a low incidence of feeding problems, with only 11% of preterm infants and 15% of full‐term infants experiencing feeding challenges in the current study.…”
contrasting
confidence: 67%
“…In this issue of Acta Paediatrica , Nieuwenhuis et al. report a similar low prevalence of feeding problems among three‐year‐old preterm infants born at less than 32 weeks of gestation and a control group of full‐term infants. Feeding problems were identified with a validated Dutch parent questionnaire and were not related to medical problems in the NICU, such as bronchopulmonary dysplasia, small‐for‐gestational age, necrotizing enterocolitis, brain injury and mechanical ventilation.…”
mentioning
confidence: 87%
“…Nieuwenhuis et al 16 used the Screeningslijst Eetgedrag Peuters (SEP), which is a validated Dutch version of the Montreal Children's Hospital Feeding Scale. This questionnaire consisted of 14 items that reflected symptoms that could be present in the feeding process, like oral motor behaviors or oral sensorial behaviors and appetite.…”
Section: Exclusion Criteriamentioning
confidence: 99%
“…Neuwenhuis et al 16 found that, at 3 years old, 11% of preterm infants had difficulty feeding. The latter is similar to what was mentioned by Jonsson et al 9 , where 7.41% of the children presented feeding problems at 3 years old, as can be seen in Table 6.…”
Section: Difficulties Experienced By Preterm Infants In Feedingmentioning
confidence: 99%
See 1 more Smart Citation